Representasi Ideologi dalam Film Dokumenter “Pulau Plastik” - Salma Nisrina Nur Fadhilah; Ferry Darmawan; Septiawan Santana (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2026)
The documentary “Pulau Plastik”  is seen as conveying the ideology reflected in the struggle of three selected activists to pressure those in authority to implement large-scale solutions to prevent environmental damage caused by waste. This study aims to examine the ideological representations reflected by the three activists using a qualitative research method with a semiotic analysis approach based on John Fiske’s model. Each finding is analyzed at three levels—the level of reality, the level of representation, and the level of ideology—to identify the meanings conveyed by the signs of opinion and ideology within the film’s advocacy framework, as shaped by the director. The research results indicate that the roles of the activists in “Pulau Plastik” serve as a medium to pressure those in authority or power, represented through the narrative of large-scale demonstrations and investigations into the abuse of power. The concept of the ideology of positional power explains that when someone holds power, they possess significant authority to regulate and direct a given environment. Meanwhile, the dissemination of ideology is evident in the concept of the “Pulau Plastik” narrative, which highlights the misconduct of certain individuals, the understanding that spheres of power will always disadvantage those without power.